Strategi Pengembangan Pemasaran dalam Menarik Minat Konsumen Pengguna Jasa di Kinipagi Wedding Planner Cirebon - Roslikawati Roslikawati; Tia Listiaty (Journal of Management and Creative Business, 2024)
The development of an increasingly advanced era has a great influence on the creative mindset of the Indonesian people and the world in all respects. The event organizer or Event Organizer (EO) service business has prospects or developments that are increasingly needed by the community, not only needed in urban areas but also in rural areas. Kinipagi Wedding Planner is one of the Wedding Organizer businesses in Cirebon which was established in 2019, precisely before the COVID-19 Pandemic in Indonesia. The data collection technique in this study uses Nonprobability Sampling technique which in this study does not provide equal opportunities or opportunities for each element of population members to be selected as sample members. The sampling technique in this study uses Purposive Sampling, which is a sampling technique with certain considerations. The research design used in this research is descriptive qualitative research design because researchers want to know how marketing development strategies and how to maintain existence to attract consumer interest in Kinipagi Wedding Planner service users. The data collection methods used in this research are observation, interviews, and documentation. results that Kinipag Wedding planner has already implemented marketing mix and has also performed SWOT analysis. The application of SWOT analytics and marketing mix on Kinipagi Wedding Planer helped have gone well especially the price factor offered is relatively cheaper compared to other wedding organizers in Cirebon. However, there were some shortcomings such as hard-to-reach locations, human resources that need to be improved, and promotional media that still have to be broadcast.